Outcomes of Closed versus Open Rhinoplasty: A Systematic Review - Rohun Gupta; Jithin John; Noopur Ranganathan; Rima Stepanian; Monik Gupta; Justin Hart; Farideddin Nossoni; Kenneth Shaheen; Adam Folbe; Kongkrit Chaiyasate (Archives of Plastic Surgery, 2022)
Open and closed rhinoplasty are two main approaches to perform nasal modifications. According to current literature, there is no current consensus among plastic surgeons and otolaryngologists on which technique is preferred in terms of aesthetic result, complications, and patient satisfaction. This study uses published research to determine whether open or closed rhinoplasty leads to superior patient outcomes. Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines for systematic reviews were followed and a literature search was conducted in four databases based on our search strategy. Articles were then imported into COVIDENCE where they underwent primary screening and full-text review. Twenty articles were selected in this study after 243 articles were screened. There were 4 case series, 12 retrospective cohort studies, 1 prospective cohort study, 1 case–control, and 2 outcomes research. There were three cosmetic studies, eight functional studies, and nine studies that included both cosmetic and functional components. Sixteen studies utilized both open and closed rhinoplasty and four utilized open rhinoplasty. Both techniques demonstrated high patient and provider satisfaction and no advantage was found between techniques. Based on available studies, we cannot conclude if there is a preference between open or closed rhinoplasty in terms of which technique leads to better patient outcomes. Several studies determined that open rhinoplasty and closed rhinoplasty leads to comparative patient satisfaction. To make outcome reporting more reliable and uniform among studies, authors should look to utilize the Nasal Obstruction and Septoplasty Effectiveness scale and the Rhinoplasty Outcome Evaluation.